Faktor-Faktor Yang Berhubungan Dengan Partisipasi Ibu Dalam Memilih Metode Kontrasepsi Metode Operasi Wanita (MOW) Di Kelurahan Pintusona Kecamatan Pangururan Kabupaten Samosir - Sinurat , Astriatalita Lastiar; Manurung, Kesaktian; Tarigan , Frida Lina; Dachi, Rahmat Alyakin; Sitorus, Mido E (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: The continuous increase in population growth is a serious concern, including in Indonesia. Samosir Regency has a Total Fertility Rate (TFR) of 3.2, higher than the provincial average (2.7), necessitating population control efforts through the use of Long-Term Contraceptive Methods (LTCM), including Female Sterilization (Tubectomy). However, mothers' participation in choosing tubectomy in Pintusona Village remains low (34.8%), influenced by factors such as knowledge, husband's support, and cultural perceptions. Objective: This study aims to analyze the factors associated with mothers' participation in choosing tubectomy as a contraceptive method in Pintusona Village, Pangururan District, Samosir Regency. Methods: This study used a cross-sectional design with a quantitative approach. The sample consisted of 70 women of reproductive age who met the inclusion criteria. Data were collected through questionnaires and analyzed using univariate, bivariate (Chi-Square test), and multivariate (logistic regression) methods.Results: Bivariate analysis showed significant associations between husband's support (p=0.003), healthcare workers' support (p=0.048), income level (p=0.000), maternal knowledge (p=0.035), and maternal attitude (p=0.024) with the selection of tubectomy. Multivariate analysis identified husband's support as the most dominant factor (OR=4.898), followed by income level. Conclusion: Husband's support and family income level are key factors influencing mothers' participation in choosing tubectomy. Family planning programs should involve husbands in education and improve access to information about tubectomy to increase its acceptance.